Clinical value of full-length tryptophanyl-tRNA synthetase for sepsis detection in critically ill patients — A retrospective clinical assessment. (August 2020) - Choi, Ji Soo; Yoon, Bo Ra; Shin, Ju Hye; Lee, Su Hwan; Leem, Ah Young; Park, Moo Suk; Kim, Young Sam; Chung, Kyung Soo
Highlights: Sepsis is a major clinical challenge in critically ill patients, involving high mortality. A biomarker is needed for the detection of sepsis to reflect the infection-related immune response. Full-length tryptophanyl-tRNA synthetase (WRS) secreted early in sepsis may be useful for the early detection of sepsis. WRS is an accurate predictive indicator of mortality in critically ill patients with sepsis. Abstract: Objectives: Related innate immune system activation and diagnostic factors of sepsis are not fully understood. The aim of this study was to analyze the clinical value of full-length tryptophanyl-tRNA synthetase (WRS) induced through inflammatory stimuli for the detection of sepsis and prediction of mortality in critically ill patients. Methods: This was a retrospective analysis of blood samples collected prospectively from patients in the medical intensive care unit (ICU) at Yonsei University College of Medicine, from March 2015 to June 2018. The ability of WRS to detect sepsis and predict mortality were compared to those of procalcitonin (PCT), C-reactive protein (CRP), and interleukin 6 (IL-6), and with Sequential Organ Failure Assessment (SOFA) and Acute Physiology and Chronic Health Evaluation II (APACHE II) scores. Results: A total of 241 study patients were enrolled, of whom 190 (78.8%) had been diagnosed with sepsis on ICU admission. The areas under the receiver operating characteristics curves (AUROCs) for sepsis discrimination with WRS, PCT, CRP, and IL-6 levels, and SOFA and APACHE II scores were 0.864, 0.727, 0.625, 0.651, 0.840, and 0.754, respectively. The prediction of 28-day mortality in patients with sepsis using WRS levels was possible and non-inferior to that with the SOFA score. Conclusions: WRS secreted early in sepsis may be useful not only for the early detection of sepsis, but also for the prediction of mortality in critically ill patients.